The Definitive Guide to Grails (Second Edition) - Rocher, Rocher (Apress, 2013)
This book is divided into 17 chapters and one appendix. Unlike the first edition, coverage of Groovy is saved for the appendix. If you have no experience using Groovy, then it is recommended that you read the appendix first as the chapters themselves dive straight into Grails starting with Chapter 1, which covers the basic philosophy behind Grails. In Chapter 2 we take you through a kick-start, demonstrating how you can quickly get productive with Grails. Then from Chapter 3 onward we delve into detailed coverage of each concept within Grails from domain classes in Chapter 3 to views in Chapter 5. By this point, you should have a good understanding of the basics. The book will then dive straight into the nitty-gritty details of Grails in Chapter 6 with coverage of URL mappings, followed by the multilingual experience that is internationalization in Chapter 7. If you haven’t had enough excitement by this point, then Chapter 8 should solve that with coverage of Grails’ support for adaptive Ajax. In Chapter 9 the book will begin to cover some of the more advanced features of Grails staring with Web Flow. In Chapter 10 you’ll get a much better understanding of how GORM works, while in Chapter 11 you’ll learn how to leverage declarative transactions with Grails services. Chapter 12 goes into a lot of detail on how you can integrate Grails into your existing ecosystem; then in Chapter 13 you will get to become a Grails plugin developer as you explore the features offered by Grails’ plugin system. Security is the focal point for Chapter 14, while in Chapter 15 we’ll cover publishing web services with Grails. Finally, Chapter 16 and Chapter 17 are dedicated to the more advanced topics of integrating Grails with the underlying Spring and Hibernate frameworks.